Estratégias discretas em teoria dos jogos - Sobrinho, Carlos Alberto Silva (2014)
In this work we have exposure to some elements of game theory and certain resolution procedures games using matrices, probability and especially optimization, ie, we optimize the moves with mathematical background. For this we will use a Theorem, two Propositions and discuss several examples to game theory, applying what we are working and show how one can proceed in several games so that the reader can understand and use such a theory. The objective is to disseminate the ideas of game theory, which has applications in several areas, including economy and military art.